2019
DOI: 10.1002/ehf2.12440
|View full text |Cite
|
Sign up to set email alerts
|

Learned helplessness reveals a population at risk for depressive‐like behaviour after myocardial infarction in mice

Abstract: Aims Myocardial infarction (MI) and heart failure (HF) are risk factors for the development of depression, additionally worsening the quality of life and patient outcome. How HF causes depression and how depression promotes HF remain mechanistically unclear, which is at least partly caused by the difficulty of in vivo modelling of psychosomatic co‐morbidity. We aimed to study the potential sequence of events with respect to different depression aspects upon HF. Methods and results Male C57BL6 mice underwent MI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…mice, while not affecting overall motility or anxiety-like behavior. In line with this, we have recently shown that HF upon MI causes a predisposition toward depressive-like behavior but not necessarily depressive-like behavior in mice [9]. Other publications have suggested experimental MI and HF as a trigger of depressive-like but not anxiety-like behavior [17,47,57].…”
Section: Ablation Of the Forebrain Mr/gr Exacerbates Depressive-like ...supporting
confidence: 78%
“…mice, while not affecting overall motility or anxiety-like behavior. In line with this, we have recently shown that HF upon MI causes a predisposition toward depressive-like behavior but not necessarily depressive-like behavior in mice [9]. Other publications have suggested experimental MI and HF as a trigger of depressive-like but not anxiety-like behavior [17,47,57].…”
Section: Ablation Of the Forebrain Mr/gr Exacerbates Depressive-like ...supporting
confidence: 78%
“…It is interesting to note that HF has also been associated with depression, and several studies have addressed this issue for example in rodent models for MI. The corresponding data suggest, however, that MI can lead to either an acute or late onset of depressive‐like phenotypes (Frey et al , 2014; Bruns et al , 2019). In our experimental setting, neither CamkIIδc TG (unpaired t ‐test; P = 0.39, n = 7/group) nor MI mice (unpaired t ‐test; P = 0.1, n = 10 sham control group; n = 8, MI group) exhibited significantly altered depressive‐like behavior when tested in the porsolt forced swim test (Agís‐Balboa et al , 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent publication, however, Bruns and coworkers analyzed the potential sequence of events with respect to different depression aspects upon heart failure in C57BL/6 mice [ 58 ]. Motility, exploration, and anxiety-like behavior were unaffected three weeks post-MI.…”
Section: Discussionmentioning
confidence: 99%